Development of electronics-free force receptor for pneumatic actuators. (3rd July 2022) - Masuda, Yoichi; Wakamoto, Ryo; Ishikawa, Masato
Abstract : Solving the issue of implementation complexity due to the increase in wiring and peripheral circuits is crucial to implement highly autonomous decentralized systems, such as the reflex system of an animal. Our study reports a novel implementation method of electronic-free reflex systems for musculoskeletal robots. The main aim of our research is to build a continuous-valued feedback system of muscle force using only mechanical pneumatic devices without bulky and expensive electrical sensors, computers, or peripheral circuits. Our system, the pneumatic reflex device, requires only a single energy line from the center to perform the control function. In this study, experiments were performed using a single-joint musculoskeletal arm to evaluate the reflex device. GRAPHICAL ABSTRACT: UF0001